2018
DOI: 10.1016/j.csbj.2018.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer Therapy Targeting Histone Methylation: Opportunities and Challenges

Abstract: Lung cancer is one of the most common malignancies. In spite of the progress made in past decades, further studies to improve current therapy for lung cancer are required. Dynamically controlled by methyltransferases and demethylases, methylation of lysine and arginine residues on histone proteins regulates chromatin organization and thereby gene transcription. Aberrant alterations of histone methylation have been demonstrated to be associated with the progress of multiple cancers including lung cancer. Inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 191 publications
(237 reference statements)
1
31
0
Order By: Relevance
“…SETDB1 is an H3K9-specific histone methyltransferase that has been described as a repressive transcription factor involved in methylation and silencing of various genes (Fei et al, 2015;Riviere et al, 2016;Karanth et al, 2017). SETDB1 levels are greatly increased in numerous cancers, including lung cancer (Lafuente-Sanchis et al, 2016;Chen B. et al, 2018), and is an important epigenetic regulator involved in control of histone methylation in tumorigenesis, dysregulation of histone methylation, and aberrant miRNA profiling, contributing to tumorigenesis and progression (Chen Y. et al, 2018;Michalak et al, 2019). Moreover, DNA methylation can directly influence miRNA biogenesis (Glaich et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…SETDB1 is an H3K9-specific histone methyltransferase that has been described as a repressive transcription factor involved in methylation and silencing of various genes (Fei et al, 2015;Riviere et al, 2016;Karanth et al, 2017). SETDB1 levels are greatly increased in numerous cancers, including lung cancer (Lafuente-Sanchis et al, 2016;Chen B. et al, 2018), and is an important epigenetic regulator involved in control of histone methylation in tumorigenesis, dysregulation of histone methylation, and aberrant miRNA profiling, contributing to tumorigenesis and progression (Chen Y. et al, 2018;Michalak et al, 2019). Moreover, DNA methylation can directly influence miRNA biogenesis (Glaich et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The most abundant histone modifications are acetylation, phosphorylation, ubiquitination and methylation by specific chromatin-modifying enzymes. Writing of methyl marks on lysine residues of histone proteins is performed by histone lysine methyl transferases, of which nine were described to be associated with lung cancer [6]. Until recently, all known histone lysine methyl transferases belonged to the su(var)3-9, enhancer-of-zeste and trithorax (SET) domain family with the only exception being DOT1L that belongs to the seven-β-strand family [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, new compounds with different mechanisms of action have been developed. Unlike the first class of DOT1L inhibitors, mimetic peptide molecules such as compound (8), shown in Figure 3, do not determine total inhibition of DOT1L activity, but bind AF9/ENL, thus blocking recruitment of DOT1L to MLL target genes and reducing levels of HOAX9 [110].…”
Section: Dot1l Inhibitorsmentioning
confidence: 99%
“…As well as modulating gene expression, this modification is involved in X-chromosome inactivation [3,4], DNA damage repair [5], and in the determination and differentiation of embryonic stem cells [6,7]. However, it is widely reported that dysregulation of HMT expression and activity is frequently observed in cancer [8][9][10][11]. Two main histone residues, arginine and lysine groups, are methylated by HMTs.…”
Section: Introductionmentioning
confidence: 99%